Kristijonas Donelaitis and Christian Gottlieb Mielcke: A Creator and his Knight - Sidabraitė, Žavinta (Senoji Lietuvos literatūra, 2014)
Christian Gottlieb Mielcke was the first contributor to Lithuanian writing who not only understood and appreciated the talent of Kristijonas Donelaitis but also undertook the publishing of fragments of his creative work. Both works in which Mielcke published parts of Donelaitis’ work appeared in Karaliaučius in 1800. These were the grammar Anfangs=Grnde einer Littau∫chen Sprach=Lehre and the bilingual dictionary Littaui∫ch=deut∫ches und Deut∫ch-littaui∫ches Wrter=Buch. In the chapter on poetics, which is a part of the grammar, Mielcke publishes eighteen lines from ‘The Autumn’s Riches’ and ‘The Cares of Winter’ and introduces Donelaitis as a talented creator. In the dictionary, Donelaitis’ narrative poem is widely used to illustrate the use of lexemes. One of the references to the source reveals that while still spreading in a manuscript form, Donelaitis’ poem was already perceived as a whole and had one unofficial title, The Seasons (Die Jahres = Ʒeiten). Presumably it was his contact with Donelaitis’ work that encouraged Mielcke to formulate, in the chapter on poetry, an innovative idea for those times that it was not possible but necessary to compose poetry in spoken Lithuanian, which was a noble language by nature. Mielcke attempted to follow Donelaitis’ example in his own poetic work. The collection of sermons Miβknygos (The Mass Books), which Mielcke prepared and published in 1800, was another proof that Lithuanian writing was turning towards the spoken language. It was an abridged translation of the postilla by Johann Gottlob Heym, which also included two original sermons by Ephraim Friedrich Meissner. The authorship of these sermons was identified having first recognized the source of the translation of the postilla. The influence of Donelaitis’ work can be discerned in Meissner’s sermons. This shows that Donelaitis’ work was known and was exploited by the contributors to the writing of Lithuania Minor as early as the end of the 18th century.
Keywords: -